Quilombos dos sertões de Crateús-CE: ancestralidades, lutas e territórios - Aires, Rosilene (2023)
Geographical Quilombamento is connection between black peoples and the territorial knowledge. In the State of Ceará, there are 87 quilombola communities distributed in 41 municipalities. Currently 50 (fithy) are certified by the Palmares Cultural Foundation (FCP) and are sekinng land tenure regularization on their lands. In this regard, I discuss the socioterritorial formation of Ceará, above all, quilombola territories of Encantados do Bom Jardim and Lagoa das Pedras, Brutos and Barriguda, located in the municipality of Tamboril. Therefore, the objective of this thesis is to discuss and to defender the right to territory of rural quilombola peoples in the socio-territorial formation of Ceará, through our ancestral cultures in the State. The methodology used comprised a qualitative approach with bibliographical, documentary and field research with scales of reflection and approach in the state, regional and municipal contexts. Observations of the quilombola daily life, semi-structured interviews, study and reflection of lectures and mappings were carried out. I outlined some forms of traditional quilombola use and occupation in mappings of the surveyed territories; finally, I understood the quilombola territories in their struggles, ancestry and their geohistorical formation, based on studies on the micro-region of Sertões de Crateús and the markers of africanities, in the municipality of Tamboril and in the quilombola territories. In this study, I considered that, in Ceará, African and Afro-Brazilian peoples faced historical erasures and silencing. The marker of Afrodiasporic ancestry in Ceará territory constitutes inherited cultural traits, for example, in the formation of quilombola territories. The marker of the collective struggle materialized in the social and political organization of the highlighted movements with influences from the Church and national and state representative entities in the reaffirmation of the rights of these peoples in Ceará. The territorial marker pointed out that the quilombos were designed from successive displacements due to enslavement and the joining of multiracial family trunks. The research contributed, therefore, to the publication of trajectories and the collective memory of the quilombola, as well as to the strengthening of struggles and identities in the quilombos of the sertões of Tamboril. The quilombola territories are,therefore, legacies of an African people that make up the social, cultural, demographic and territorial formation of Ceará.